Correlation Between Total Cholesterol, HDL, and Non-HDL Cholesterol with Apolipoprotein B in Hyperlipidemia Patients - Laily Shofiyah; Maria Galuh Kamenyangan Sari; Novianto Adi Nugroho; Adji Suwandono; Niken Dyah Aryani Kuncorowati; Risalina Myrtha; Hendrastutik Apriningsih; Nurhasan Agung Prabowo; Tonang Dwi Ardyanto; Frieska Dyanneza (Poltekkes Kemenkes Surabaya, 2026)
Hyperlipidemia is a major modifiable risk factor for atherosclerotic cardiovascular disease. Among the available laboratory markers, non-HDL cholesterol and apolipoprotein B have attracted considerable attention as more informative measures of the true atherogenic burden carried by a patient’s blood. 51 hyperlipidemia patients were recruited sequentially for our cross-sectional study at the Clinical Laboratory of UNS Hospital, Sukoharjo. A power calculation for correlation studies (α = 0.05, power = 80%) was used to estimate the sample size. A TMS 30i analyser was used to quantify total cholesterol, HDL, and apo B; non-HDL cholesterol was calculated by subtraction. For every association, Pearson product-moment correlation coefficients with 95% confidence intervals (CIs) were calculated using Fisher's z-transformation. There was a high and positive correlation between total cholesterol and apo B (r = 0.881, 95% CI: 0.803–0.932, p < 0.001). There was no significant correlation between HDL cholesterol and apo B (r = 0.082, 95% CI: −0.196 to 0.349, p = 0.566). Apo B and non-HDL cholesterol had the highest correlation by far (r = 0.938, 95% CI: 0.896–0.963, p < 0.001). In hyperlipidemic, non-HDL cholesterol followed apo B more accurately than any other parameter, supporting its usage as a useful, affordable substitute for apo B in situations when direct measurement is not possible. To strengthen these relationships, larger, prospective, multi-center studies that account for important variables are required.